2021
DOI: 10.3389/fpsyg.2021.726864
|View full text |Cite
|
Sign up to set email alerts
|

How Does It Feel to Be Online? Psychotherapists’ Self-Perceptions in Telepsychotherapy Sessions During the COVID-19 Pandemic in Italy

Abstract: Aims: The COVID-19 pandemic and consequent extreme restrictions imposed by governments across the world forced psychotherapists to abruptly change their working modality. The first aim of the current study was to assess psychotherapists’ self-perceptions (i.e., affective and cognitive perceptions about their self and their self in relation to clients) when providing telepsychotherapy during the first peak of the COVID-19 pandemic in Italy. The second aim was to explore the associations between psychotherapists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 55 publications
(76 reference statements)
1
21
0
2
Order By: Relevance
“…Surprisingly, many answers at t1 but only a few at t2 indicate that psychotherapists suffer from constraints regarding full-sensory perception of their patients during remote psychotherapy sessions. Psychotherapists seem to adapt and enhance their skills in remote psychotherapy over time, as Mancinelli et al (2021) have similarly observed in Italian psychotherapists during the pandemic. With curfews imposed again at test period t3 in Fall 2020, the previously positive attitude changed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Surprisingly, many answers at t1 but only a few at t2 indicate that psychotherapists suffer from constraints regarding full-sensory perception of their patients during remote psychotherapy sessions. Psychotherapists seem to adapt and enhance their skills in remote psychotherapy over time, as Mancinelli et al (2021) have similarly observed in Italian psychotherapists during the pandemic. With curfews imposed again at test period t3 in Fall 2020, the previously positive attitude changed.…”
Section: Discussionmentioning
confidence: 57%
“…Even though psychotherapists experienced some professional self-doubt or anxiety and worry about technicalities and therapeutic relationship in the early phase of the pandemic in 2020, they reported a relatively good working alliance and strong real relationship with their patients in a remote setting (Aafjes-van Doorn et al, 2020). Despite reports of more directive and talkative behavior, a study by Mancinelli et al (2021) shows an overall positive self-perception in psychotherapists.…”
Section: Therapeutic Relationshipmentioning
confidence: 99%
“…The additional mental demands entailed by the lack of visual information, the removal of expected cues and the need for abstraction also help to explain why participants, and other research studies (Cantone et al, 2021;Mancinelli et al, 2021), found remote therapy even more effortful than face to face therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Therapists can feel under-skilled due to a lack of specific training and standardized ways of working and have doubts about the efficacy of remote therapy (Bee et al, 2016;Turner et al, 2018;Knott et al, 2020;McBeath et al, 2020). Two key concerns were a lack of confidence in managing risk (Fisher et al, 2020) and feeling particularly fatigued during remote therapy (Cantone et al, 2021;Mancinelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians delivering telepsychotherapy have reported concerns about their ability to be authentically and emotionally connected with their clients, as well as their ability to be as effective as they would if providing mental health services in a traditional therapy setting. 22 , 23 However, research has proven the efficacy of this modality, which enables psychotherapists and patients in separate locations to see each other and interact synchronously in real-time. Our study findings are also supported by experimental studies showing that the perceived distance between two interacting individuals modulates the empathic reaction between them, which is a key ingredient in all psychotherapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%